Influence of iron precursors on catalytic wet oxidation of H2S to sulfur over Fe/MgO catalysts - Lee, EK; Jung, KD; Joo, OS; Shul, YG (ELSEVIER, 2005)
The Fe/MgO catalysts prepared from iron nitrate, iron chloride and iron sulfate were studied for catalytic wet oxidation Of H2S to sulfur. They were characterized using BET, XRD, H-2-TPR and TG/DSC techniques. Catalysts prepared from iron nitrate showed the highest H2S removal ability among the prepared catalysts. Both the TPR and XPS analyses of the catalysts indicate that H2S removal ability correlates with the dispersion of iron oxide in the Fe/MgO catalysts prepared from different iron precursors. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: SELECTIVE OXIDATION; ELEMENTAL SULFUR; DEHYDROGENATION; XPS